'Las juventudes' rising: Argentina's local, global and innovate youth activism - Seca, María Victoria (2022)
There are multiple discoursestheworld over about young people,what they should do andwhat they shouldn’t do, that reflectstereotypical views and stigmatisation. Butwhy do youth get involved in politics,what are their agendas and howdo they actively take part in and make theworld? In Argentina over the past 20 years, young people have become politicalsubjects, and social protest based on collective action and participation,with a strong youth component, has developed. Our research is grounded in theoretical approachesto the sociology of youth and collective action,such as that of Carles Feixa, Geoffrey Pleyers, Pablo Vommaro and Melina Vázquez, butwhat dowe mean by young people?It isworth noting that in Spanish,we speak of youth (“lasjuventudes”) in the plural, because there is no singleway of being young. The basic question “what is a young person” has often been asked,sometimes highlighting positive aspects and sometimes negative ones.Neither isthe truth. The experiences of young people are diverse and determined by multiple factorssuch as gender, nationality, religion, ethnicity and place. Sowhat motivatesthe young to get involved?Howdo they expresstheirsocial and political commitment? Looking at the past 20 years,what are the generational agendas of youth participation in Argentina?